2019
DOI: 10.3390/ma12223704
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive In Vitro Testing of Calcium Phosphate-Based Bioceramics with Orthopedic and Dentistry Applications

Abstract: Recently, a large spectrum of biomaterials emerged, with emphasis on various pure, blended, or doped calcium phosphates (CaPs). Although basic cytocompatibility testing protocols are referred by International Organization for Standardization (ISO) 10993 (parts 1–22), rigorous in vitro testing using cutting-edge technologies should be carried out in order to fully understand the behavior of various biomaterials (whether in bulk or low-dimensional object form) and to better gauge their outcome when implanted. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 284 publications
(343 reference statements)
0
28
1
Order By: Relevance
“…Generally, antibacterial ability conflicts with biocompatibility. Therefore, to evaluate the biocompatibility of protamine/HAp, in vitro cytotoxicity tests were carried out according to ISO 10993-5:2009 “Tests for Cytotoxicity—In vitro Methods” [ 20 ]. Human osteoblastic cells (MG-63) were cultured in extracts from various kinds of powders (0.1 mg·mL −1 ) for 24 and 72 h. As shown in Figure 7 , the results of the MTT assay at 24 and 72 h showed that no significant changes of cell viability were seen in concentrations ranging from 125 to 500 μg·mL −1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, antibacterial ability conflicts with biocompatibility. Therefore, to evaluate the biocompatibility of protamine/HAp, in vitro cytotoxicity tests were carried out according to ISO 10993-5:2009 “Tests for Cytotoxicity—In vitro Methods” [ 20 ]. Human osteoblastic cells (MG-63) were cultured in extracts from various kinds of powders (0.1 mg·mL −1 ) for 24 and 72 h. As shown in Figure 7 , the results of the MTT assay at 24 and 72 h showed that no significant changes of cell viability were seen in concentrations ranging from 125 to 500 μg·mL −1 .…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate the antibacterial activity, Escherichia coli (E. coli, ATCC 27325) and Staphylococcus aureus (S. aureus, ATCC 6538) were used in this study. Bacteria were grown in a culture broth (nutrient USA) supplemented with 10% heat-inactivated fetal bovine serum (Sigma, St. Louis, MO, USA) and 0.1% antibiotics (penicillin-streptomycin solution, Sigma) in a humidified atmosphere containing 5% CO 2 at 37 • C. According to ISO 10993-5:2009 "Tests for Cytotoxicity-In vitro Methods" [20], extracts were obtained in a separate culture medium (0.1 g•mL −1 of the culture medium for 24 h at 37 • C). For cytotoxicity test, cells were seeded at 5 × 10 3 cells•well -1 on 96-well plates and cultured for 24 h at 37 • C/5% CO 2 .…”
Section: Antimicrobial Evaluationmentioning
confidence: 99%
“…Because THP‐1 cells, a cell line of human monocyte cells, were used in the present study, we could evaluate not only the behavior of cells against the biomaterials but also the behavior of cells involved in the inflammatory immune process for protecting tissues from toxins and initiating the resolution of inflammation 30 . Monocyte recruitment and differentiation may occur in the tissue in response to calcium phosphate‐based biomaterials 31 . Additionally, macrophages are the principal cells responsible for mediating the proinflammatory response toward implant debris as a precursor of osteoclasts 32 …”
Section: Discussionmentioning
confidence: 99%
“…30 Monocyte recruitment and differentiation may occur in the tissue in response to calcium phosphate-based biomaterials. 31 Additionally, macrophages are the principal cells responsible for mediating the proinflammatory response toward implant debris as a precursor of osteoclasts. 32 Previous studies showed the variable effect of the size and shape of nanostructured HA particles on cellular viability.…”
Section: Discussionmentioning
confidence: 99%
“…The process of bone regeneration integrated with bioceramics consists on different steps that can be summarized as a complex and multistage process resulting from a plethora of biological stages; including osteogenesis, angiogenesis and inflammatory responses. All these processes are essential for the recovery of tissue homeostasis and function 13 but for them to occur a good biocompatilibity between the bioceramic and the nearby tissue is essential 12,16 .…”
mentioning
confidence: 99%